A crítica de Thomas Reid à teoria das ideias em René Descartes - Gonçalves, Angela (2021)
The objective of this work is to show Thomas Reid's criticism of the theory of ideas, in particular, the theory of ideas in René Descartes, to analyze the two theories and to defend that the theory of ideas does not incur skepticism, and furthermore, to show that Reid does not understood Descartes' epistemology. So, the problem to be investigated is whether the theory of ideas really incurs skepticism, whether Reid understood Descartes and making the case for Descartes' theory of ideas. To this end, it shows how Reid presents Descartes in his book entitled “Investigation of the Human Mind according to the Principles of Common Sense” and in his work “Essay on the Intellectual Powers of Men”. Firstly, the aspects mentioned by Reid about Descartes' disbelief in the material world, Reid's critique of the ideas of the senses, the author's criticism of images and impressions in the mind that Descartes defends are shown in the first work mentioned above, and finally, Reid's defense of analogies and conjectures that lead the theory of ideas to error is presented. In the Essays on the Intellectual Powers of Men, Reid presents mental operations in more depth and continues to criticize the fallacy of the senses, the theory of perception in Descartes and presents Reid's theses against the theory of ideas and what they are. the causes for this theory to fall into skepticism. Subsequently, Thomas Reid's epistemology and his “philosophy of common sense” are presented as an alternative to Cartesian skepticism. Reid is considered a realistic philosopher, because he advocates a form of direct realism for sensitive knowledge through conception-perception as a form of knowledge. The theory of reidian evidence is explained, explaining mental acts such as conception, perception, senses, belief, memory. In addition, Reid's method, "induction", is presented, what it is and how it works based on the Regulae Philosophandi which, for the author, are the maxims of common sense, as they are used in people's daily lives. Still, it explains what the general theory of common sense is. In another moment, the Cartesian method is presented and what are the ideas for Descartes, because it is the core of his representationism. An explanation of the theory of Cartesian evidence is made explaining memory, perception, imagination, conception and the senses. It explains what the theory of ideas is also and how the access between mind and material world occurs. Finally, it is argued that the theory of ideas does not incur skepticism, arguments and theses are presented for this support; the theory of common sense would be a first degree of knowledge, the theory of ideas a higher degree for defending ideas, representation.